2001
DOI: 10.3758/bf03192898
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous discrimination learning: Stimulus interactions

Abstract: Stimulus Similarity EffectsThe degree of physical similarity between the S1 and the S during the acquisition of a discrimination has played an important role in theories of discrimination learning (see, e.g., Lawrence, 1955;Logan, 1966;Spence, 1937). By making certain assumptions-(1) that the excitatory strength of the S1 is greater than the inhibitory strength of the S ; (2) that the shape of the generalization gradient is concave downward; and (3) that the net effect can be represented by the algebraic summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Although the participants did rank the high-effort SϪ stimuli as better than the low-effort SϪ stimuli, when given a choice between high-effort SϪ stimuli and low-effort SϪ stimuli, no significant difference was found. Clement et al attributed the preference for the SϪ stimulus that followed greater effort to the transfer of value from the Sϩ to the SϪ stimuli in each discrimination (see Zentall & Clement, 2001). But other research has found no evidence for a preference for the SϪ stimulus that followed greater effort (Clement & Zentall, 2002;DiGian et al, 2004;Friedrich et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Although the participants did rank the high-effort SϪ stimuli as better than the low-effort SϪ stimuli, when given a choice between high-effort SϪ stimuli and low-effort SϪ stimuli, no significant difference was found. Clement et al attributed the preference for the SϪ stimulus that followed greater effort to the transfer of value from the Sϩ to the SϪ stimuli in each discrimination (see Zentall & Clement, 2001). But other research has found no evidence for a preference for the SϪ stimulus that followed greater effort (Clement & Zentall, 2002;DiGian et al, 2004;Friedrich et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…In research with pigeons, we have sometimes found a preference for the S stimulus similar to the preference for the S stimulus that followed the less-preferred event in training (Clement et al, 2000), but in several other experiments a preference for the S stimulus has not been found (DiGian et al, 2004;Friedrich et al, 2005). When we have sometimes found such an S preference, we have explained it in terms of value that may transfer from an S to an S in a simultaneous discrimination (Zentall & Clement, 2001). However, we have also suggested that the reason the S effect is often not found is that reliable value transfer effects occur primarily when the S stimuli themselves have a greater difference in absolute value (e.g., differential probability of reinforcement) than they do in the present design.…”
Section: Testingmentioning
confidence: 99%
“…Nonetheless, recent analyses of discrimination learning suggest that other associative factors may also contribute to performance. Specifically, Zentall and his associates (Zentall & Clement, 2001;Sherburne, 1994) andvon Fersen et al (1991) have proposed that the S in a simultaneous discrimination acquires some positive or excitatory value from the S which it accompanies. Stated otherwise, some of the value that directly accrues to an S via reinforced responding to it transfers to the S with which it is presented.…”
mentioning
confidence: 99%